2020
DOI: 10.1186/s12970-020-0336-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined protein and calcium β-hydroxy-β-methylbutyrate induced gains in leg fat free mass: a double-blinded, placebo-controlled study

Abstract: Background: The leucine metabolite β-hydroxy-β-methylbutyrate (HMB) is widely used as an ergogenic supplement to increase resistance-training induced gains in fat free mass (FFM) and strength in healthy adults. Recent studies have questioned the effectiveness of HMB, particularly when a high protein diet is habitually consumed. To investigate the additive resistance-training induced effects of HMB and protein in untrained individuals, we conducted a randomized double-blind, placebo-controlled study that compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…However, the placebo group in Stahn et al [39] (ingesting 30 g whey protein only) did not actually show a significant increase in whole-body FFM. Therefore, the conclusions of that study [39] are perplexing, since it would be expected that 12 weeks of RET would result in a significant increase in whole-body FFM even in the placebo group [9,44]. Nevertheless, the fact that HMB is not effective in producing significant effects in young subjects performing resistance exercise does not exclude the possibility of potential effects in other populations or physiological states.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, the placebo group in Stahn et al [39] (ingesting 30 g whey protein only) did not actually show a significant increase in whole-body FFM. Therefore, the conclusions of that study [39] are perplexing, since it would be expected that 12 weeks of RET would result in a significant increase in whole-body FFM even in the placebo group [9,44]. Nevertheless, the fact that HMB is not effective in producing significant effects in young subjects performing resistance exercise does not exclude the possibility of potential effects in other populations or physiological states.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it is not known if the acute effects of HMB on protein synthesis [15,16] are additive to the expected response to the ingestion of proteins or a resistance exercise bout, but it would seem unlikely so long as leucine was ingested at a sufficient dose [15]. Nevertheless, some studies [2,3,9,39], including one from our group [9], have tested the long-term effects of ingesting HMB together with high-quality protein on the adaptation to resistance exercise. Two of these studies [3,9], showed no significant benefit to body composition changes or strength gains caused by RET of adding HMB to protein-containing nutritional supplements, 75 g and 50 g respectively [3,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HMB has been shown to improve strength and fatigue resistance in quadriceps muscles of humans including the elderly in multiple studies especially when HMB treatment was combined with exercise [ 53 , 95 , 103 , 126 130 ]. However, we did not observe an increase in muscle force or fatigue resistance in the EDL muscles of Ca-HMB-treated rats after unloading by HS or during reloading as compared to rats that received water.…”
Section: Discussionmentioning
confidence: 99%